2006
DOI: 10.1371/journal.ppat.0020065
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated B. pertussis as a Single-Dose Nasal Vaccine against Whooping Cough

Abstract: Pertussis is still among the principal causes of death worldwide, and its incidence is increasing even in countries with high vaccine coverage. Although all age groups are susceptible, it is most severe in infants too young to be protected by currently available vaccines. To induce strong protective immunity in neonates, we have developed BPZE1, a live attenuated Bordetella pertussis strain to be given as a single-dose nasal vaccine in early life. BPZE1 was developed by the genetic inactivation or removal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
179
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 46 publications
8
179
0
14
Order By: Relevance
“…Protection against B. pertussis was comparable with that induced by two injections of acellular vaccine in adult mice and was significantly better than that induced by two administrations of acellular vaccine in infant mice (3). Moreover, histopathological and physiological studies in mice confirmed that B. pertussis BPZE1 is highly attenuated, although it is still able to transiently colonize the mouse respiratory tract and thereby induce strong protection upon a single intranasal administration (4).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Protection against B. pertussis was comparable with that induced by two injections of acellular vaccine in adult mice and was significantly better than that induced by two administrations of acellular vaccine in infant mice (3). Moreover, histopathological and physiological studies in mice confirmed that B. pertussis BPZE1 is highly attenuated, although it is still able to transiently colonize the mouse respiratory tract and thereby induce strong protection upon a single intranasal administration (4).…”
mentioning
confidence: 70%
“…Studies in mice have shown that the live attenuated B. pertussis strain BPZE1 is a promising candidate as a new effective pertussis vaccine for young children (3)(4)(5)16). Preclinical proof of concept has been established in murine models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…pertussis in which PT gene was deleted was reported to be attenuated by its inability to cause severe infection in mice without affecting the ability of the bacteria to colonize the respiratory tract and protect mice against challenge with the wild type. 140 More recently, a live attenuated B. pertussis mutant strain (BPZE1) in which PT was genetically detoxified PT, dermonecrotoxin [DNT] gene deleted and B. pertussis ampG replaced by E. coli ampG to minimize its activity, was reported to induce protection in young mice after a single nasal administration 141 and reported to be safe in adult interferon-γ receptor deficient adult mice. 142 However, this strain survived in lungs as long as the wild type strain.…”
mentioning
confidence: 99%